A werewolf's guide to seducing a vampire - Hawley, Sarah ([Glimmer falls], 2024)
"Ben Rosewood never meant to be bound to a vampire succubus, especially one as sexy yet terrifying as Eleonore Bettencourt-Devereux, but he has to admit there are some fang-tastic perks. . . . Werewolf Ben Rosewood is happy with his life. One hundred percent. Everything is fine. His business, Ben's Plant Emporium, is thriving, and he's even expanding the shop. His anxiety disorder is . . . well, it's been better, but that comes with the territory of running a business and having beastly urges every full moon, right? As for romance--who has the time? Though his family is desperate to see him settled, Ben is fine approaching forty as a single werewolf. But after drunkenly bidding on and winning a supposedly possessed crystal on eBay one night, he finds himself face-to-face with a beautiful yet angry vampire. Eleonore Bettencourt-Devereux is a rare breed--a vampire succubus born from two elite European bloodlines during medieval times. Thanks to an evil witch, she's been stuck in a crystal since she was thirty, forced to obey orders from the possessor of the rock. Eleonore's been dreaming of breaking the spell and severing the witch's head for centuries. But did the witch really sell her to someone new and for only ninety-nine cents? Eleonore would claw this werewolf's heart out and eat it, if only the binding spell would allow her. But Eleonore and Ben soon realize they can help each other with both vengeful and less-hostile needs. And why not have a little fun along the way?"--